PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI MINUMAN DI BLU BAR DE VINS SKY HOTEL SEMINYAK BALI - Ni Luh Gede Eka Wintari; I Ketut Sutapa; Ni Wayan Mekarini (Universitas Triatma Mulya, 2021)
This study aims to analyze the impact of promotion and brand image of consumer' decision to buy drinks at Blu Bar de Vins Sky Hotel Seminyak, Bali since tight competation arise among providers to attract costumers. The study stated five problems such as partial impact of promotion and brand image, simultaneously impact of these variables, the stonger variable in impacting consumer' decision and the amount of these variables impact. The population in this study were consumers of Blu Bar de Vins Sky Hotel Seminyak, Bali with a total sample of 90 respondens. Data collected by questioner, interview and documentation then analyzed by multiple linear regression analysis. Based on the results of analysis, there are five conclusions, such as (a) Promotion had positive and significant impact to consumer' decision to buy drinks at Blu Bar; (b) Brand image had positive and significant impact of consumer' decision to buy drinks at Blu Bar; (c) Promotion and brand image simultaneously had positive and significant impact to consumer’ decisions in buying drinks at Blu Bar; (d) Brand image brings more impact in influencing consumer decisions to buy drinks at Blu Bar; and (e) Promotion and brand image bring 77,4 % impact to consumer' decision to buy drinks at Blu Bar de Vins Sky Hotel Seminyak, Bali de Vins Sky Hotel Seminyak, Bali. Thus, the rest 23,6 % could be influenced by other factors such are prize and location which are not studied in this research.